Batik Tamarin Empowering Woman in Patimban Subang Indonesia - Arleti M. Apin; Belinda Sukapura Dewi; Ariesa Pandanwangi; Nuning Damayanti (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2020)
Patimban, a new port to help the inadequate sea passage of the Tanjung Periuk port in Jakarta. The location of this port is in the north of Java Island in Subang. With regard to the construction of this port, of course it will have an impact on the activities of the local community, who are dominant as fishpond fishermen. The Ministry of Transportation, through its dharma women, collaborates with a team of presenters open up economic opportunities for the local community. From several alternatives, the batik tamarin technique was chosen for fisherwives, this technique is relatively cheap and safe so it is very appropriate for them to learn. It is proven that in a short time they have been able to master this technique, big hopes for them to be able to develop it and economic opportunities will open up.